PENGARUH KUALITAS WEBSITE, NILAI YANG DIRASAKAN, KEPERCAYAAN DAN KEAMANAN TERHADAP KEPUASAN KONSUMEN PADA SHOPEE - Made Reyvaldo; Muinah Fadhilah; Agus Dwi Cahya (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to test whether customer satisfaction can be influenced by website quality, perceived value, convenience and security. The sampling method is non-probability sampling while the sampling technique uses a purposive sample. This study took samples from Shopee customers who were over 17 (seventeen) years old and had made purchases at Shopee more than 2 (two) times. Collecting data in this study using a questionnaire that will be distributed via google form. The number of questionnaires to be processed is 95 questionnaires. Data were processed using SPSS software version 26. Data analysis used multiple linear analysis. The results of this study indicate that: (1) website quality has no positive and significant effect on customer satisfaction, (2) perceived value has a positive and significant effect on customer satisfaction, (3) trust has a positive and significant effect on consumer satisfaction,(4) security has no positive and significant effect on consumer satisfaction